2012
DOI: 10.1038/ijo.2012.172
|View full text |Cite
|
Sign up to set email alerts
|

High energy expenditure masks low physical activity in obesity

Abstract: Objective To investigate energy expenditure in lean and obese individuals, focusing particularly on physical activity and severely obese individuals. Design Total daily energy expenditure (TDEE) was assessed using doubly labeled water, resting metabolic rate (RMR) by indirect calorimetry, activity EE (AEE) by difference and time spent in physical activity by multisensor activity monitors. Subjects 177 lean, Class I and severely obese individuals (age 31–56, BMI 20–64 kg/m2). Results All components of EE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 49 publications
5
50
0
3
Order By: Relevance
“…No such research exists for adults but it seems plausible that overweight/obese adults require a higher amount of rest during sports participation. The present study showed that overweight/obese spend more time in sedentary pursuits during waking hours compared with nonoverweight participants, which is consistent with previous research (Scheers et al 2012; DeLany et al 2013). The association between exercise and sedentary time in the present study, however, was low.…”
Section: Discussionsupporting
confidence: 93%
“…No such research exists for adults but it seems plausible that overweight/obese adults require a higher amount of rest during sports participation. The present study showed that overweight/obese spend more time in sedentary pursuits during waking hours compared with nonoverweight participants, which is consistent with previous research (Scheers et al 2012; DeLany et al 2013). The association between exercise and sedentary time in the present study, however, was low.…”
Section: Discussionsupporting
confidence: 93%
“…These devices have been shown to provide accurate for estimation of a variety of activities . In addition, we have previously observed lower minutes of moderate to very vigorous activity, greater steps/days, and greater time spent in sedentary behavior in the severely obese, which corresponded to a lower AEE .…”
Section: Methodsmentioning
confidence: 73%
“…Although obese people have a lower physical activity level compared with lean people, their physical activity EE tends to be higher (DeLany et al 2013). A previous study demonstrated that the energy costs of some light activities were proportional to body weight (Schoeller and Jefford 2002).…”
Section: Discussionmentioning
confidence: 98%